La question du logement social à New York - Catherine Pouzoulet (Transatlantica)
This paper focuses upon the debates that took place in New York City in the early years of the La Guardia administration around the issue of low‑income public housing. It outlines the separate, conflicting agendas of various actors (such as housing reformers, trade‑unionists, social workers, real estate developers, business groups…), and analyzes how their positions interacted with the struggle for control of the newly created public housing program between the federal and local governments. Prior to the Depression, government involvement in the working‑class housing market had been unacceptable in a city which had left a free rein to private investors and had only reluctantly adopted a zoning regulation in 1916, essentially to remedy the excesses of unfettered speculation as they undermined real‑estate investments. At the same time, New York City had become sadly famous for housing unrivalled numbers of its working‑class and immigrants in unhealthy, dilapidated tenements. Successive tenement regulations had generated wide publicity and helped initiate a national housing movement but failed to provide a marked improvement in the living conditions of poor people. As long as new dwellers came pouring into poor neighborhoods, slum landlords were in a position to control the housing market and take advantage of record‑high densities. The Depression created a radically new context. For the first time, slum neighborhoods had a high vacancy rate, and the collapse of the housing market allowed housing reformers to step in and make alternative proposals, advocating innovative architectural concepts as well as ideas for decommercializing residential property. The combination of a progressive administration at local level (La Guardia) and a liberal upsurge at federal level (Roosevelt and the New Deal) created the conditions for government engagement in the production of low‑income housing. The upgrading of housing for the poor was seriously discussed but these debates were also rapidly marked by diverging views. The creation in 1934 of the first local authority (NYCHA) to build public housing was to serve as a model for the creation of a federal housing authority (USHA) as part of the 1937 Wagner‑Steagall Act. These years of experimentation saw a rapid evolution in the production of housing under the auspices of local and federal authorities. The initial impetus to build innovative, low‑density, low‑rise projects and to conceive a universal housing policy that did not stigmatize alternative housing for the poor was soon eclipsed by the higher concerns of other political and economic actors to upgrade working‑class neighborhoods and generate new profits. In particular, the debates about site selection pitted those who advocated a decentralized, low‑scale approach against those who pushed for slum clearance in central neighborhoods. By 1938, with the creation of a City Planning Commission, a bifurcation of the New York City housing market was well in place, with government subsidies of private housing for the white middle class on attractive sites, and substandard public housing for the poor in degraded neighborhoods disdained by private investors. Ultimately, the utopian vision of modern, decent housing for all as well as the concern for community building were defeated by the political and economic forces who favored the building of high‑density, high‑rise, low‑cost public projects. In the postwar era, these projects were to become repositories of crime and delinquency and reinforce existing patterns of racial segregation, thus further contributing to the deterioration of inner‑city neighborhoods. The bifurcation of the housing market at local level paralleled a dual approach of the federal government. The 1930’s—and the political forces at work behind the scenes at local and federal level—were thus to shape the decades to come as the initial vision of a unified federal housing program was defeated by the emergence of a two‑tiered approach. While the federal government undertook the production of low‑cost housing for the poor, it also heavily subsidized the suburbanization process by providing aid to the private housing market. Whereas political support for the lower tier of public housing for the poor soon eroded, the upper tier of federal programs for the middle class became more entrenched along the years. The early years of public housing in New York City therefore demonstrate how New Deal programs were altered by the in‑put of local politics and how the initial vision of New Dealers, heavily influenced by European reformers, was compromised within a few years.